Comparison Study of Embankment Filled with Selected Material and Foamed Mortar on Toll Road - Yudhi Lastiasih; Indrasurya B. Mochtar (Himpunan Ahli Teknik Tanah Indonesia, 2022)
The road studied was planned to be constructed on an embankment with a height ranging from 3 to 12 meters. It also has compressible soil conditions at a thickness of ± 10 meters and an average N-SPT value ranging from 5 to 12 which indicates a relatively large soil compression. Therefore, it is necessary to design a road embankment that meets the standard safety factor by using lightweight materials to minimize the occurrence of subgrade compression. The effect of gravel and foam mortar materials on the settlement and stability of the embankment was determined using 4 combinations including 100% gravel, 25% foam mortar with 75% gravel, 50% foam mortar with 50% gravel, and 75% foam mortar and 25% gravel. The findings showed that the combination with higher content of foam mortar has a smaller settlement and overall stability considered to be safe. It was discovered that the combination of 75% foam mortar and 25% gravel was able to reduce the settlement up to 0.6 times and increase the average safety factor up to 1.46 times. This combination was found to have the best results with consolidation settlement (Sc) of 1,24 m and Safety Factor (SF) of 1,383 for STA 414+525 while the values for STA 424+576 were 0,42 m and 2,78, respectively.